Formulation and development of paediatric orally disintegrating carbamazepine tablets - R Canadell-Heredia; M Suñé-Pou; A Nardi-Ricart; P Pérez-Lozano; JM Suñé-Negre; E García-Montoya (Saudi Pharmaceutical Journal, 2022)
Carbamazepine is a medicine used to manage epilepsy and partial or tonic-clonic seizures. This study aimed at formulating and obtaining carbamazepine orodispersible tablets for paediatric use at a 50 mg dose, with a diameter not greater than 6 mm and a tablet weight of 80 mg, through a direct compression process. The SeDeM pre-formulation/formulation method was used to define the characteristics of both carbamazepine and the selected excipients for direct compression. This study succeeded in formulating and obtaining the proposed tablets. Following the application of the SeDeM method, the tablets met the mass uniformity test and showed appropriate hardness values for orodispersible tablets. The tablets also met the United States Pharmacopeia (USP) test specifications at t = 60 min. The orodispersible tablets obtained may improve compliance with paediatric treatment with carbamazepine, ensuring the safety and effectiveness of the medicine.